Photocatalytic degradation of methyl orange dye by ZnO/TiO2/CoFe2O4 trapped in alginate beads - Miraso, Marvelous Nzwanai (Midlands State University, 2019)
Azo dyes have become an immerging and difficult pollutant to the environment. Industrial activities have resulted in disposal of these toxic dyes in effluent and among them is methyl orange (MO) dye. Proper effluent treatment schemes have become a necessity so as to be able to reduce the potential toxicity issues regarding plant and animal life due to the rise in demand for clean and safe water. Several methods have been applied for the removal and degradation of MO dye but have proven to be inadequate. The purpose of this work was photocatalytic degradation of MO by a novel composite catalyst ZnO/TiO2/CoFeO4. ZnO was synthesized by sol-gel and CoFe2O4 via the co-precipitation method ZnO, CoFe2O4 and commercial TiO2 was combined and trapped in alginate ZnO/TiO2/CoFe2O4 was characterized for functional groups, thermal stability, size, morphology and surface crystallinity. Successful fabrication was shown by the presence of the O-H stretching, C-H stretching and the M-O stretching vibrations on the FTIR spectrum. The composite was thermally stable and the photocatalysts constituted 9% of the composite. Optimum conditions were pH 8, 240 min and 0.2 g catalyst dosage. The effective initial concentration was 10 mg/L. Complete decolorisation of 10 mg/L under optimum conditions giving up to 98.4% degradation. The mechanism of photocatalysis was indirect. The composite was stable as there was no change in the percentage composition in terms of the catalysts added which were 1.9% ZnO and 6.7% CoFe2O4 in both the recycled and the fresh composite. The composite can be reused up to 5 cycles giving significant degradation.